The cancer factory : industrial chemicals, corporate deception, and the hidden deaths of American workers - Morris, Jim (Beacon Press, 2024)
"The story of a group of Goodyear Tire and Rubber workers fatally exposed to toxic chemicals, the lawyer who sought justice on their behalf, and the shameful lack of protection our society affords all workers. A gripping narrative in the tradition of A Civil Action and Toms River"--